COMMUNICATIVE CULTURE AS A SUCCESS FACTOR BUSINESS COMMUNICATION IN THE MANAGEMENT SYSTEM - Черушева, Галина (SWorldJournal, 2023)
The article discusses the conceptual foundations of communication culture, defines the key role of communication in the management system, reveals the essence of the concept of "communication competence" and its structural components. Based on the analysi